The real acoustic power of a planar annular membrane radiation for axially-symmetric free vibrations - RDZANEK, W.J.; RDZANEK, W.P. (Archives of Acoustics, 1997)
The real part of the acoustic power radiated by a planar annular membrane is considered for axially-symmetric free vibrations. The membrane is located in a planar, rigid baffle and radiate acoustic wave into a lossless and homogeneous fluid medium. Sinusoidal in time processes are examined. The real power is obtained as elementary form for high-frequency radiated waves.